A Narrative Review on Etiology and Mechanism of Aflatoxin B1 in the induction of Hepatocellular Carcinoma (Journal of Pharmaceutical Negative Results, 2022)
Hepatocellular carcinoma is one of the primary liver cancer. Even though the incidence of HCC differs among various geographic regions, ethnicity, gender and age, it is one of the most common malignancies among Asian and African populations. It is well represented as the fourth most common cancer in the world. It is estimated that more than 80% of HCC cases are attributed due to viruses including hepatitis B and C infections. However it is also quite interesting that consumption of hazardous alcohol, dietary exposure of aflatoxin1 and hemochromatosis are also highly associated with the initiation and development of HCC. Risk factors such as AFB1 could alter the DNA upon exposure, modify the proteins and induce oxidative stress and further leading to malignant transformation of the hepatocytes. In this review we narrated the basics of the etiology and molecular mechanisms behind the involvement of AFB1 in the initiation and development of hepatocellular carcinoma.